Oral contraceptive use and mortality after 36 years of follow-up in the Nurses' Health Study: prospective cohort study. (31st October 2014) - Charlton, Brittany M; Rich-Edwards, Janet W; Colditz, Graham A; Missmer, Stacey A; Rosner, Bernard A; Hankinson, Susan E; Speizer, Frank E; Michels, Karin B
Abstract : Objective To determine whether use of oral contraceptives is associated with all cause and cause specific mortality. Design Prospective cohort study. Setting Nurses' Health Study, data collected between 1976 and 2012. Population 121 701 participants were prospectively followed for 36 years; lifetime oral contraceptive use was recorded biennially from 1976 to 1982. Main outcome measures Overall and cause specific mortality, assessed throughout follow-up until 2012. Cox proportional hazards models were used to calculate the relative risks of all cause and cause specific mortality associated with use of oral contraceptives. Results In our population of 121 577 women with information on oral contraceptive use, 63 626 were never users (52%) and 57 951 were ever users (48%). After 3.6 million person years, we recorded 31 286 deaths. No association was observed between ever use of oral contraceptives and all cause mortality. However, violent or accidental deaths were more common among ever users (hazard ratio 1.20, 95% confidence interval 1.04 to 1.37). Longer duration of use was more strongly associated with certain causes of death, including premature mortality due to breast cancer (test for trend P<0.0001) and decreased mortality rates of ovarian cancer (P=0.002). Longer time since last use was also associated with certain outcomes, including a positive association with violent or accidental deaths (P=0.005). Conclusions All cause mortality did not differ significantly between women who had ever used oral contraceptives and never users. Oral contraceptive use was associated with certain causes of death, including increased rates of violent or accidental death and deaths due to breast cancer, whereas deaths due to ovarian cancer were less common among women who used oral contraceptives. These results pertain to earlier oral contraceptive formulations with higher hormone doses rather than the now more commonly used third and fourth generation formulations with lower estrogen doses.